Guadalupe Aqueduct in Mexico City. Legal Protection of a Historical Monument (London Journal of Research In Humanities and Social Sciences, 2024)
The author focuses her analysis on the issue of the preservation of immovable historical monuments, the constructions built during the 16th to 19th centuries in Mexico. Legal instruments exist to this end, but other factors converge to facilitate, hinder or even prevent the legal and technical protection of the properties inquestion. As well as to sensitise the communities that inhabit or safeguard historic monuments towards the mutual benefit of both the property and the society that owns it. The reading emphasises the importance of consulting the documentation in the Jorge Enciso Historical Archive and Plan Library, which contains information on the different interventions and changes in the use of historic buildings.
Keywords: Nikolai Marr; glottogenesis; labor; tool of labor; manual (linear; kinetic) language; sound language.; Convergence; Research Creation; Interdisciplinarity; Semillero.; students; knowledge; drug abuse; Information; sources; undergraduate